First molecular detection of piroplasmids in non-hematophagous bats from Brazil, with evidence of putative novel species - Ikeda, Priscila [UNESP]; Menezes, Taline Revollo [UNESP]; Torres, Jaire Marinho; de Oliveira, Carina Elisei; Lourenço, Elizabete Captivo; Herrera, Heitor Miraglia; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Springer Nature, 2021)
Piroplasmida is an order of the phylum Apicomplexa that comprises the Babesia, Cytauxzoon, and Theileria genera. These hemoparasites infect vertebrate blood cells and may cause serious diseases in animals and humans. Even though previous studies have shown that bats are infected by different species of piroplasmids, the occurrence and diversity of these hemoparasites have not been investigated in this group of mammals in Brazil. Therefore, the present work aimed to investigate the occurrence and assess the phylogenetic placement of piroplasmids infecting bats sampled in a peri-urban area from Central-Western Brazil. Seventeen (12.6%) out of 135 animals were positive by nested PCR assay for the detection of Babesia/Theileria targeting the 18S rRNA gene. Eleven sequences of the 17 positive samples could be analyzed and showed an identity of 91.8–100% with Theileria bicornis, Babesia vogeli, a Babesia sp. identified in a small rodent (Thrichomys pachyurus) from the Brazilian Pantanal and a Babesia sp. identified in a dog from Thailand as assessed by nBLAST. A phylogenetic tree was constructed from an alignment of 1399 bp length using analyzed and known piroplasmid 18S rRNA sequences. In this tree, piroplasmid 18S rRNA sequences detected in three specimens of Phyllostomus discolor (Piroplasmid n. sp., P. discolor) were placed as a sister taxon to Theileria sensu stricto (Clade V) and Babesia sensu stricto (Clade VI). An additional phylogenetic tree was generated from a shorter alignment of 524 bp length including analyzed piroplasmid 18S rRNA sequences of bat species Artibeus planirostris and A. lituratus (Piroplasmid sp., Artibeus spp.). The two 18S rRNA sequences detected in Artibeus spp. (Piroplasmid n. sp., Artibeus spp.) were placed within Babesia sensu stricto (Clade VI) into a strongly supported clade (bootstrap: 100) that included Babesia vogeli. The two 18S rRNA sequences of Piroplasmid sp., Artibeus spp. showed a single and a two-nucleotide differences, respectively, with respect to B. vogeli in a 709 pb length alignment. For the first time, the present study shows the occurrence of putative new piroplasmid species in non-hematophagous bats from Brazil.
Keywords: 18S rRNA; Babesia; Chiroptera; Piroplasmida